2009
DOI: 10.1007/s10997-009-9086-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the compensation level of outside director depend on its personal profile? Some evidence from UK

Abstract: Corporate governance, Board of directors, Outside director, Remuneration policy, G3, G2, J44,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 69 publications
5
38
1
1
Order By: Relevance
“…Those studies have mainly focused on the adoption of performance-based remuneration to reduce the potentially misaligned interest between shareholders and INEDs (e.g., Hempel and Fay, 1994;Boyd, 1996;Bryan, Hwang, Klein & Lilien , 2000;Cordeiro et al, 2000) or the adoption of meeting fees to provide INEDs with an incentive to exert more effort (Hempel and Fay 1994;Bryan et al 2000;Brick, Palmon & Waldet, 2006;Farrell, Friesen & Hersch, 2008;Adams and Ferreira 2008). A more comprehensive agency theory framework was adopted by Cordeiro et al (2000), Andreas et al (2012) and Marchetti & Stefanelli (2009). These studies still rely on an optimal contracting perspective of agency theory, but consider not only firm performance and meeting fees as potential determinants of INEDs' remuneration but also INEDs' roles within the board and firm complexity.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Those studies have mainly focused on the adoption of performance-based remuneration to reduce the potentially misaligned interest between shareholders and INEDs (e.g., Hempel and Fay, 1994;Boyd, 1996;Bryan, Hwang, Klein & Lilien , 2000;Cordeiro et al, 2000) or the adoption of meeting fees to provide INEDs with an incentive to exert more effort (Hempel and Fay 1994;Bryan et al 2000;Brick, Palmon & Waldet, 2006;Farrell, Friesen & Hersch, 2008;Adams and Ferreira 2008). A more comprehensive agency theory framework was adopted by Cordeiro et al (2000), Andreas et al (2012) and Marchetti & Stefanelli (2009). These studies still rely on an optimal contracting perspective of agency theory, but consider not only firm performance and meeting fees as potential determinants of INEDs' remuneration but also INEDs' roles within the board and firm complexity.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to this perspective, inter-directorial differences in remuneration may rather stem from taking on additional functions and responsibilities (e.g., chairmanship or committee membership) or variations in meeting attendance (Hempel & Fay, 1994;Brick et al, 2006;Farrell et al, 2008;Marchetti & Stefanelli, 2009), although Cordeiro et al (2000) found mixed evidence between outside (non-executive) director's remuneration and measures of director's effort. However overall we would expect that the effort that an INED expends is usually directly related to his/her responsibilities in the board (Linck et al, 2009;Engel, Hayes & Wang, 2010).…”
Section: Hypotheses' Developmentmentioning
confidence: 99%
See 3 more Smart Citations